The Effect of Professional Education and Training for Teachers (PLPG) in Improving Pedagogic Competence and Teacher Performance - Yusnita, Yeni; Eriyanti, Fitri; Engkizar, Engkizar; Anwar, Fuady; Putri, Nofrina Eka; Arifin, Zainul; Syafril, Syafrimen (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
This study is aimed at analyzing the effect of Professional Education and Training for Teachers (PLPG) in improving pedagogic competence and teacher performance. The research used quantitative method through survey approach. The data was taken from 35 respondents using the training exam module and teacher performance instruments. All data were analyzed using software SPSS for Windows release 22.0 through both descriptive and correlation analysis. The result of descriptive analysis of teachers pedagogic competence after taking training test is good (83,74%). Furthermore, Pearson Product Moment Correlation analysis shows that there is a significant negative correlation between these activities and teachers performance obtained (rcount) = -0.590 at 0.000 significance level. The results of the analysis show that teachers need to follow the training to improve their pedagogic competence as well as their performance in teaching and assessing. Since the teachers’ knowledge increases, it will definitely have an impact on their performance at school.